2016
DOI: 10.1016/j.ijppaw.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of taeniid ( Taenia spp., Echinococcus spp.) eggs contaminating vegetables and fruits sold in European markets and the risk for metacestode infections in captive primates

Abstract: Due to frequent cases of alveolar echinococcosis (AE) in captive primates in Europe, 141 samples of food, which consisting of vegetables and fruits, were investigated for contamination with egg-DNA of taeniids. Each sample consisted of at least 40 heads of lettuce as well as various vegetables and fruits. The samples were purchased at different times of the year: either from September to November (autumn), originating from greenhouses or fields in the Basel region in the North of Switzerland, or in April and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 41 publications
1
48
1
4
Order By: Relevance
“…multilocularis and E. granulosus s.l. is still ongoing (Federer et al., ; Lass et al., ; Robertson et al., ). Two recent reviews and meta‐analyses suggested that the chance of AE and CE transmission through the ingestion of food and water contaminated with E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…multilocularis and E. granulosus s.l. is still ongoing (Federer et al., ; Lass et al., ; Robertson et al., ). Two recent reviews and meta‐analyses suggested that the chance of AE and CE transmission through the ingestion of food and water contaminated with E .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the debate on the importance of unwashed contaminated fresh fruit, vegetables and mushrooms in the transmission of E. multilocularis and E. granulosus s.l. is still ongoing (Federer et al, 2016;Lass et al, 2016;Robertson et al, 2016). Two recent reviews and meta-analyses suggested that the chance of AE and CE transmission through the ingestion of food and water contaminated with E. multilocularis and E. granulosus eggs does exist, but potential risk factors associated with foodborne and waterborne transmission do not significantly increase the risk of infection to humans Conraths et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in Jordan involving 55 patients infected with CE, revealed that, in addition to contact with animals through their occupation, many also consumed raw vegetables [35]. Eating unwashed vegetables is a risky practice that potentially increases exposure to Echinococcus, as well as other canine zoonotic diseases [36,37]. A study in Turkey identified a variety of canine parasite eggs on unwashed vegetables, including Taenia spp.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that a single taeniid egg (T. hydatigena) contains around 7000 mitochondrial targets, and the detection limit of PCRs targeting the mitochondrial DNA was estimated at 33 copies [10•]. In our lab, a reliable method combining sieving (eggs retained in a 20-μm sieve), microscopy, multiplex PCR on DNA from taeniid-positive samples (egg-DNA PCR) and optionally confirmatory sequencing was developed [10•, 51] aiming to differentiate eggs of E. granulosus s.l., E. multilocularis and other taeniids, and the method has extensively been used for individual diagnosis (e.g., [54,60,61]) and in studies investigating field-collected specimens (see below). However, molecular analyses of taeniid eggs can also be performed after isolation with classical diagnostic sedimentation/flotation procedures [62,63].…”
Section: Diagnosis Of Intestinal Taeniid Infections By Fecal Examinationmentioning
confidence: 99%
“…e, f Immature eggs showing a thin embryophore and no oncosphere; e was stored for 8 months in saline solution at 4°C and f was freshly removed from an adult specimen of E. multilocularis infecting a fox from the ground [92], though such a contamination cannot be excluded as flies were shown to transmit such eggs [26]. A second investigation on the presence of cestode eggs in feed (vegetables, fruits) [60] was triggered by frequent cases of alveolar echinococcosis in primates kept in captivity at a Zoo. Egg-DNA PCR using multiplex PCR/sequencing [10•] on filtered samples revealed non-zoonotic Taenia spp.…”
Section: Determination Of Food Contaminationmentioning
confidence: 99%